Molecular Detection of Gene Mutation Related to Drug Resistance in Mycobacterium leprae - Saumya Shukla; Shaina Gaikwad; Dhandapani Sureshgopi; Vivek Kumar Chouksey; Chandrashekhar Pathe; Jerene Mathews; Jitendra Singh; Shashank Purwar; Debasis Biswas; Pushpendra Singh; Anand Kumar Maurya (International Journal of Mycobacteriology, 2025)
Background: Mycobacterium lepare-induced leprosy continues to pose a significant public health threat. Drug-resistant strains pose a major challenge for effective management, necessitating molecular studies to identify resistance-associated mutations and guide appropriate therapy. Methods: A cross-sectional analysis of a total of 47 samples, including slit-skin smear and biopsy specimens, were collected along with relevant clinical details. Fifteen samples that tested positive for acid-fast bacilli were further processed. Amplification of folP1, rpoB and gyrA genes was performed using polymerase chain reaction, followed by automated capillary sequencing to identify mutations associated with dapsone, rifampicin, and ofloxacin resistance, respectively, in M. leprae. Results: Sequencing revealed no folP1 and rpoB gene mutations in any of the 15 isolates sequenced in this study, indicating wild-type status and susceptibility to dapsone and rifampicin, respectively. A mutation was identified at codon 91 (alanine [GCA] → valine [GTA]) in the gyrA gene (20%), resulting in an alanine-to-valine change known to cause resistance to ofloxacin. Five samples did not provide adequate chromatogram quality for analysis. Conclusion: The study identified mutations in the gyrA gene which is associated with ofloxacin resistance in M. leprae in Central India. While the absence of resistance to first-line anti-leprosy drugs is reassuring, the emergence of resistance to fluoroquinolones is a cause for concern. Early detection of resistant strains facilitates prompt initiation of drug therapies, reducing their spread and advancing the global leprosy eradication effort.